Ausschüttungssperre nach § 268 Abs. 8 HGB - Kaya, Devrimi; Borgwardt, Lena (Unternehmensteuern und Bilanzen, 2010)

Befreiende Wirkung des Konzernabschlusses einer ausländischen Komplementärgesellschaft - Kaya, Devrimi (Internationale und kapitalmarktorientierte Rechnungslegung, 2010)

Computergestützte Textanalyse von erweiterten Bestätigungsvermerken - Kaya, Devrimi; Seebeck, Andreas (Die Wirtschaftsprüfung, 2018)

Corporate Culture and M&A Deals: Using Text from Crowdsourced Employer Reviews to Measure Cultural Differences - Hertel, Tobias; Kaya, Devrimi; Reichmann, Doron (Journal of Banking & Finance, 2024)
Corporate culture constitutes a key success factor in mergers and acquisitions (M&A). We examine the role of acquirer-target cultural differences in US domestic M&A deals. We train a topic model on how employees describe corporate culture in free-response texts of crowdsourced employer reviews to estimate cultural differences between the acquirer-target pairs. We find a negative linear relationship between cultural differences and deal announcement returns. However, adding a squared term of our main variable of interest to our model reveals a U-shaped relationship between cultural differences and announcement returns that is stronger in magnitude and statistical significance than the single term alone. Our study reconciles two competing hypotheses on the role of cultural differences in M&
Keywords: Cultural difference; M&A; Employer reviews; LDA

Countries adoption of the International Financial Reporting Standard for Small and Medium-sized Entities (IFRS for SMEs) - Early empirical evidence - Kaya, Devrimi; Koch, Maximilian (Accounting and Business Research, 2015)
The International Financial Reporting Standard for Small and Medium-sized Entities (IFRS for SMEs) is increasingly being adopted in a number of jurisdictions. Despite the economic importance of non-publicly accountable entities, little is known about what factors influence countries' decisions to adopt IFRS for SMEs. In a unique sample of 128 countries, we find that countries that are not capable of developing their own local generally accepted accounting principles are more likely to adopt IFRS for SMEs. We also provide evidence that in jurisdictions where full IFRS have been applied to private firms, the likelihood of adoption of IFRS for SMEs increases, suggesting that jurisdictions reduce the financial reporting burden on SMEs. Moreover, in line with prior literature, there is evidence that countries with a relatively low quality of governance institutions are more likely to adopt this new set of accounting standards. The results also hold under alternative measures and different estimation approaches. Overall, our results are helpful in understanding the worldwide diffusion of IFRS for SMEs. Standard setters and regulators might consider our study in the future development of accounting harmonisation of non-publicly accountable entities.
CRIS-Team Scopus Importer:2024-03-11
Keywords: Accounting harmonisation; Accounting regulation; IASB; IFRS for SMEs; Nonpublicly accountable entities; Standard setting

Der Prüfungsmarkt von nicht-kapitalmarktorientierten Konzernen – Eine Analyse der Marktstruktur und Abschlussprüferhonorare - Freiberg, Jens; Kaya, Devrimi; von der Lippe, Hendrik; Voskuhl, Luis (Der Betrieb, 2024)

Deskriptive Analyse zur Übernahme des IFRS for SMEs aus Ländersicht - Kaya, Devrimi; Lutterberg, Theresa (Internationale und kapitalmarktorientierte Rechnungslegung, 2016)

Die Aussagekraft des Lageberichts mittelständischer Unternehmen – Handlungsempfehlungen unter Berücksichtigung empirischer Ergebnisse - Kaya, Devrimi (Unternehmensteuern und Bilanzen, 2010)

Die Vollhafterlösung bei einer GmbH & Co. KG zur Vermeidung der Jahresabschlusspublizität - Kaya, Devrimi; Kaya, Zekiye (NWB - Steuer- und Wirtschaftsrecht, 2010)

Digitale Finanzberichterstattung in (i)XBRL – Empirische Analyse zur Taxonomienutzung von US-amerikanischen Unternehmen - Kaya, Devrimi; Glachtsiou, Petroula; Schulz-Weidner, Anett (Internationale und kapitalmarktorientierte Rechnungslegung, 2021)

Empirical Capital Market Research on Conference Calls: A Literature Review Empirische Kapitalmarktforschung zu Conference Calls: Eine Literaturanalyse - Kaya, Devrimi; Maier, Christian; Böhmer, Tobias (Schmalenbach Journal of Business Research, 2020)
Over the last decades, conference calls held in conjunction with an earnings release have become an important instrument for disclosure on capital markets. This paper reviews the empirical literature on the determinants and economic consequences of conference calls. We structure our literature review around topics such as the access to conference calls, the participation and capital market reactions. In addition, we review studies, which examine the phenomenon conference call to gain important insights into the information content of conference calls as well as the communication behavior of participants. Finally, our review identifies opportunities for future research. The literature review includes 49 studies from highly-ranked international journals between 1998 and 2018.
CRIS-Team Scopus Importer:2024-03-11
Keywords: Capital market communication; Conference calls; Earnings call; Literature review

Empirische Analyse des Offenlegungszeitpunkts von Jahresabschlüssen nach dem EHUG - Henselmann, Klaus; Kaya, Devrimi (2008)
The paper analyses the timing of disclosing financial statements for small and medium enterprises (SME) in Germany in 2007 and 2008. Comparisons of different regional areas and different company sizes are made and possible explanations for the results discussed. – Rechnungslegungspolitik ; Publizitätsverhalten ; Größenklassen ; Kleine und Mittlere Unternehmen (KMU) ; Elektronisches Unternehmensregister

Empirische Analyse des Offenlegungszeitpunkts von Jahresabschlüssen nach dem EHUG - Henselmann, Klaus; Kaya, Devrimi (Die Wirtschaftsprüfung, 2009)

Entry and capital structure mimicking in concentrated markets: The role of incumbents’ financial disclosures - Bernard, Darren; Kaya, Devrimi; Wertz, John (Journal of Accounting & Economics, 2021)
We examine whether the public availability of product market incumbents' financial disclosures leads to greater capital structure mimicking of incumbents by entrants. Exploiting a change in disclosure enforcement for German private firms in the mid-2000s, we find entrant-incumbent mimicking rises substantially in concentrated markets once incumbents' financial statements are publicly available. Additional tests exploring potential mechanisms are more consistent with interfirm learning underlying the effect than alternative channels. Our findings shed light on the effects of competitor financial statement disclosure on private firms’ initial financing decisions and highlight how capital structure dependencies among peer firms arise.
CRIS-Team Scopus Importer:2024-03-11
Keywords: Capital structure; Disclosure; Mimicking; Private firms; Product markets

ESG-Strategie im Mittelstand – mehr Governance wagen? Analyse der Aufsichtsrats- und Beiratsbildung - Kaya, Devrimi; von der Lippe, Hendrik; Hennig, Philipp (Der Betrieb, 2023)

European Single Access Point: die künftige zentrale EU-Datenbank für Unternehmensinformationen - Kaya, Devrimi; Glachtsiou, Petroula; von der Lippe, Hendrik; Kosmowski, Dorian (Die Wirtschaftsprüfung, 2022)

Kommentierung § 291 HGB Befreiende Wirkung von EU/EWR-Konzernabschlüssen - Henselmann, Klaus; Kaya, Devrimi (Systematischer Praxiskommentar Bilanzrecht, 2010)

Kommentierung § 322 HGB Bestätigungsvermerk - Henselmann, Klaus; Kaya, Devrimi (Handbuch Bilanzrecht, 2010)

Offenlegungspraxis im Mittelstand seit dem EHUG - Kaya, Devrimi; Scherr, Elisabeth (BBK - Betrieb und Rechnungswesen, 2010)

Out-of-sample predictability of firm-specific stock price crashes: A machine learning approach - Kaya, Devrimi; Reichmann, Doron; Reichmann, Milan (Journal of Business Finance & Accounting, 2024)
We use machine learning methods to predict firm-specific stock price crashes and evaluate the out-of-sample prediction performance of various methods, compared to traditional regression approaches. Using financial and textual data from 10-K filings, our results show that a logistic regression with financial data inputs performs reasonably well and sometimes outperforms newer classifiers such as random forests and neural networks. However, we find that a stochastic gradient boosting model systematically outperforms the logistic regression, and forecasts using suitable combinations of financial and textual data inputs yield significantly higher prediction performance. Overall, the evidence suggests that machine learning methods can help predict stock price crashes.
Created from Fastlane, Scopus look-up
Keywords: machine learning; natural language processing; stock price crash risk; textual disclosures

Potential Adoption of IFRS by the United States: A Critical View - Kaya, Devrimi; Pillhofer, Julian A. (Accounting Horizons, 2013)
This paper discusses the potential adoption of International Financial Reporting Standards (IFRS) by the United States (U.S.). We use the reporting decisions of foreign U.S. listed firms as signals for U.S. capital markets' accounting standard preferences and demand for financial information. Our analysis of the 2009 (2010) annual reports filed with the SEC reveals that only 19 (23) percent of all foreign issuers file IFRS reports, although the reconciliation to U.S. GAAP requirement was eliminated in 2007. Thus, our results indicate that the majority of foreign filers in 2009 and 2010 use U.S. GAAP disclosure practices. Moreover, we provide evidence that cross-listed firms rarely change their filing behavior over the two-year sample period. Our analysis shows that the International Accounting Standards Board (IASB) is subject to problems connected with its structure and its limitations as a non-governmental organization (NGO). Therefore, we call for caution toward IFRS adoption by the SEC. We conclude by recommending an international treaty to provide better funding and oversight of the IASB and that steps are taken to harmonize enforcement of accounting standards around the world. Our analysis should be of interest to regulators, standard setters, national authorities, and companies interested in the current debate on a global set of accounting standard
WiSo-Import:2015-03-26:4738
Keywords: IFRS; US GAAP; SEC

Rechnungslegungspublizität inländischer Zweigniederlassungen von Auslandsgesellschaften - Kaya, Devrimi; Zenk, Florian (Internationale und kapitalmarktorientierte Rechnungslegung, 2011)

Rechnungslegungspublizität von (Schein-)Auslandsgesellschaften - Kaya, Devrimi; Zenk, Florian (Internationale Wirtschaftsbriefe, 2010)

Shortseller und Unternehmensreaktionen: Der Fall Adler Group S.A. - Kaya, Devrimi; Glachtsiou, Petroula; von der Lippe, Hendrik; Voskuhl, Luis (Der Betrieb, 2022)

Size management by European private firms to minimize proprietary costs of disclosure - Bernard, Darren; Burgstahler, David; Kaya, Devrimi (Journal of Accounting & Economics, 2018)
We examine size management by European private firms for which disclosure requirements increase at size thresholds. Our estimates suggest at least 8% of firms near thresholds that impose income statement disclosure manage size downward, and the average firm that manages size sacrifices more than 6% of its assets. We find that multiple determinants of proprietary costs predict this behavior, and that size management to avoid mandatory audits, which are similarly imposed at size thresholds, is of comparable magnitude. Our results triangulate the economic significance of proprietary costs in a setting largely without confounding capital market, agency, or compliance costs.
CRIS-Team Scopus Importer:2024-03-11
Keywords: Disclosure; Mandatory audit; Private firms; Proprietary costs; Size management

Strategien zur Jahresabschlusspublizität im Mittelstand – Handlungsempfehlungen unter Berücksichtigung empirischer Ergebnisse - Kaya, Devrimi; Scherr, Elisabeth (BBK - Betrieb und Rechnungswesen, 2010)

Strategien zur Verminderung und Vermeidung der Jahresabschlusspublizität - Kaya, Devrimi; Scherr, Elisabeth (BBK - Betrieb und Rechnungswesen, 2010)
WiSo-Import:2015-04-13:1658
Keywords: Forschungsbericht 2010; Kohäsion

The benefits of structured data across the information supply chain: Initial evidence on XBRL adoption and loan contracting of private firms - Kaya, Devrimi; Pronobis, Paul (Journal of Accounting and Public Policy, 2016)
A growing body of literature documents how different parties benefit from structured data across the information supply chain. The purpose of this study is to examine the effect of voluntary adoption of the eXtensible Business Reporting Language (XBRL) on price and non-price terms of loan contracting. Using a sample of Belgian private firms, the analyses provide evidence that banks charge lower interest rate spreads to voluntary adopters as compared to non-adopters. The results also show that loan sizes are larger in comparison for voluntary adopters of XBRL. Further, the effect of XBRL adoption is stronger for opaque firms. The results are robust to using different estimation approaches as well as additional tests. The findings are in line with the view that XBRL data filings reduce information processing costs, and contribute to our understanding of the impact of structured data on loan contracting – an implication that may be of interest to regulators and other parties interested in the benefits of structured data across the information supply chain.
CRIS-Team Scopus Importer:2024-03-11

The dissemination of firm information via companyregister websites: Country-level empirical evidence - Kaya, Devrimi; Seebeck, Andreas (Journal of Accounting and Organizational Change, 2019)
Purpose: The purpose of this paper is to investigate the cross-country determinants of the extent of firm information disseminated via company register (CR) websites. Design/methodology/approach: The authors develop an index model (CR score) designed to capture the extent of regulated firm information disseminated via CR websites. The proposed index is applied to a unique sample of 137 countries. Following prior literature, the proposed index covers three dimensions: data availability, data accessibility and data serviceability. The index composition and the URLs of the CR websites are provided as an exhibit to this paper. Findings: Across a variety of tests and sample compositions, the authors find consistent evidence that countries with a relatively high level of internet penetration, those that facilitate cross-border trading and those with higher governance quality show higher CR scores. The results are generally in line with theories of regulation. Practical implications: The results of this paper speak directly to the current regulatory initiatives which aim to foster information acquisition and processing via company registers. Originality/value: The authors provide early empirical evidence on the cross-country variation of dissemination of firm information via CR websites for a unique sample of 137 countries. Investors, analysts and other users of financial statements should be aware of the underlying factors that influence the extent and accessibility of firm information.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Company registers; Firm data dissemination; Open data; Public interest; Regulation

The influence of firm-specific characteristics on the extent of voluntary disclosure in XBRL: Empirical analysis of SEC filings - Kaya, Devrimi (International Journal of Accounting and Information Management, 2014)
Purpose - The purpose of this paper is to empirically investigate the influence of several firm-specific characteristics on the extent of voluntary disclosure in eXtensible business reporting language (XBRL). Design/methodology/approach - A disclosure checklist consisting of 54 financial and non-financial items in XBRL format is developed to examine the extent of voluntary disclosure in the 2008 annual reports of 51 US listed firms. Findings - The results show that firm size and firms' level of innovativeness are significantly and positively related to the extent of overall disclosures. Research limitations/implications - There are, however, several limitations in the study. First, a relatively small sample size of 51 firms from the year 2008. Second, the construction of an unweighted disclosure index based on the elements, which were voluntarily disclosed, may not be the best measurement. It might be interesting to replicate this study based on a larger sample size from another voluntary filing program. Originality/value - The findings of this study should be of interest to firms that prepare, "clients" that use and regulators that monitor financial reporting disclosures in XBRL. © Emerald Group Publishing Limited.
CRIS-Team Scopus Importer:2024-03-11
Keywords: Accounting; Disclosure index; FASB; Financial reporting; SEC; Voluntary disclosure; XBRL

Theorie und Praxis des Value Reporting am Beispiel der Prognoseberichterstattung im Konzernlagebericht - Kaya, Devrimi (Der Konzern, 2010)
WiSo-Import:2015-03-26:1659
Keywords: Forschungsbericht 2010; Kohäsion

The Power of Words: An Empirical Analysis of the Communicative Value of Extended Auditor Reports - Seebeck, Andreas; Kaya, Devrimi (European Accounting Review, 2023)
We examine the communicative value of extended auditor reports in the United Kingdom (UK), where ISA 700 (UK and Ireland) requires auditors to disclose the risks of material misstatement that had the greatest effect on the audit–key audit matters (KAM). By using methods from computational linguistics, we find that different proxies for communicative value (i.e., readability, evaluative content, visual aids, and specificity) improve in post-ISA 700 periods. Cross-sectional tests show that the improvement differs across audit firms and audit clients as well as KAM disclosure characteristics. Finally, broadly consistent with concurrent studies, we find no evidence that several proxies for communicative value are informative to investors. However, we find initial evidence that a more specific description of KAM is significantly and positively associated with capital market reactions, suggesting that investors value precise information. Overall, this study directly responds to the call for more research on how KAM are worded.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Communicative value; Critical audit matters (CAM); Extended auditor reporting; Key audit matters (KAM); Specificity; Textual analysis

The Role of Non-Governmental Organizations (NGOs) as Intermediaries of the European Union Decision to Adopt International Accounting Standards: 1973-2002 - Kaya, Devrimi; Kirsch, Robert; Henselmann, Klaus (Accounting Historians Journal, 2016)

Ursachen des Offenlegungsdefizits von Jahresabschlüssen nach dem EHUG: Ergebnisse einer empirischen Untersuchung - Henselmann, Klaus; Kaya, Devrimi (Zeitschrift für Corporate Governance, 2009)

Vermeidung der Jahresabschlusspublizität durch Auslandsgesellschaften: Das Zweigniederlassungsmodell als strategischer Handlungsansatz - Henselmann, Klaus; Kaya, Devrimi; Meichelbeck, Hugo (Zeitschrift für Corporate Governance, 2010)

Zur Offenlegungspraxis von Prüfungshonoraren bei Genossenschaftsbanken und Sparkassen - Kaya, Devrimi; Loy, Thomas; Zentgraf, Daniel (Die Wirtschaftsprüfung, 2018)